Occurrence of gastrointestinal parasites from Friesian cattle in Pekan - Mat Yusof, Afzan (Microscopy Society Malaysia, 2019)
Gastrointestinal parasitic infections in cattle causes a reduction in production and affect the cattle’s health. A study was carried out to investigate the parasite infection in cattle from commercial farm in Pekan, Pahang. A total of 152 Friesian cattle and calf samples were collected and examined by direct smear technique, simple flotation, and sedimentation techniques to determine parasite loads in different age groups. Parasitic eggs seen in cattle feces with the highest prevalence was Eimeria spp. (56.58%), followed by Strongyle spp. (9.87%), Strongyloides spp. (1.32%) and Ascaris spp. (0.66%). Calves below 6 months (85%) were more infected with parasites than older ones. This study shows that the most common parasite among Friesian cattle was Eimeria spp., so an effective farm management system and antiprotozoal treatment should be conducted to control the parasitic infections in cattle farms.